MAFIAT: Magnetic field analysis tools - Price, D. J.; Pomoell, J.; Kilpua, E. K. J. (Frontiers in Astronomy and Space Sciences, 2022)
The magnetic twist is one of the key defining parameters of solar flux ropes (FRs). The routine computation of the winding of magnetic field lines, referred to as the twist, has the potential to lead to significant advancement in the field of solar physics and solar - terrestrial research, e.g., by enabling more accurate investigations of FR morphology, stability, and temporal evolution. However, this has been hampered by the axial-dependence of the solution and the availability of simpler, albeit approximate, methods. Here we introduce the Magnetic Field Analysis Tools (MAFIAT) python library and Jupyter notebooks for the computation and exploitation of this quantity. The required axis location is specified manually by the user, either with their own preferred method, or using the twist number calculated from the parallel current by MAFIAT. The notebooks allow users to create a variety of novel visualisations of FRs and their twist distributions for scientific study. MAFIAT is written in Python and is released under the BSD 3-Clause Licence.